Adaptation and psychometric properties of the Multigroup Ethnic Identity Inventory in secondary education - S. Suherman; T. Vidákovich (Образование и наука)
Introduction. The research demonstrates that the Multigroup Ethnic Identity Inventory (MEI2) is an effective tool for assessing various aspects of ethnic identification among Indonesian secondary school students from diverse ethnocultural backgrounds. Aim. The aim of this study is to examine the impact of ethnic identity on the psychological well-being of secondary school students in Indonesia, utilising the MEI2 questionnaire. Methodology and research methods. The study involved 276 secondary school students (60.1% female; 39.9% male). Data were analysed using the SPSS software version 29 and SmartPLS v4. Confirmatory Factor Analysis (CFA) was utilised to evaluate how well the measurement model fits the data. Results and scientific novelty. The CFA validated the MEI2, with the goodness-of-fit index indicating that the model was both efficient and appropriate. The Kaiser-Meyer-Olkin (KMO) value was .885. Consistency reliability measured by Cronbach’s alpha (α), ranged from .69 to .85, and composite reliability, assessed by McDonald’s (ω), ranged from .64 to .83. Discriminant validity was observed with a range from .591 to .696. Consequently, significant positive correlations were identified among the three domains of ethnic identity. Practical significance. The study supports the MEI2 as a valid instrument for assessing ethnic identity among Indonesian secondary school students. It also assists educators in recognising and addressing the diverse ethnic identities of students within the context of Indonesian culture.